Écriture auto-ethnographique et positionnement: réflexivité entourant l’arabité et le queer - Bouqentar, Lamiae (Alterstice, 2021)
Cet article est un texte réflexif sur mon recours à une écriture auto-ethnographique dans ma recherche doctorale à propos de la migration arabe queer. En tant que chercheure arabe queer migrante, je puise dans la notion de positionnement, qui permet de considérer les expériences des groupes minorisés et racialisés comme une source pertinente de savoir. Inspirée de la tradition auto-ethnographique, je procède en incluant des fragments de récit de soi tirés de mes propres échanges de la vie, pour ainsi problématiser les identifications arabe et queer composant mon positionnement.
Keywords: 2000 à aujourd'hui; 2020-2029; LGBTQIA2+; afrique; amériques; approches et analyses; arts; autoethnographie; canada; communication; cours; discipline; féminisme décolonial; histoire et politique; intersectionnalité; maroc; montréal; premier cycle; périodes historiques; queer; québec; rabat; régions géographiques; sex2283; thématiques; études culturelles; études littéraires

Afropea: utopie post-occidentale et post-raciste - Miano, Léonora (Bernard Grasset, 2020)
Léonora Miano n'est pas une Afropéenne (afro-européenne). Ceux qui se définissent ainsi ont grandi en Europe.Marquée par l'Afrique subsaharienne, la sensibilité de l'auteur se distingue de celle des Afropéens. Ceux-ci se sont construits en situation de minorité. Ce qui détermine la perception de soi, complique l'identification et la solidarité entre Afropéens et Subsahariens.La France identifie à l'Afrique tous ses citoyens d'ascendance subsaharienne, privilégiant les natifs de ce continent. Cela ne favorise pas l'ancrage des Afropéens dans leur pays, leur capacité à se sentir responsables de son destin.Pourtant, ceux qui se sont donné un nom - Afropéens - dans lequel Afrique et Europe fusionnent, s'ils sont fidèles aux implications de cette association plus qu'à leur amertume, peuvent incarner un projet de société fraternel, anti-impérialiste et anti-raciste. Dans une France en proie aux crispations identitaires, la perspective afropéenne apparaît encore comme une utopie. De part et d'autre, la tentation du rejet est puissante.
Keywords: afrique; afrique subsaharienne; afro-féminisme; antiracisme; approches et analyses; arts; com5170; cours; discipline; europe; france; féminisme afropéen; féminisme décolonial; histoire et politique; premier cycle; régions géographiques; thématiques; utopie; études littéraires

Indigenous women and feminism: politics, activism, culture - Suzack, Cheryl; Huhndorf, Shari M.; Perreault, Jeanne; Barman, Jean (Women and indigenous studies series, 2010)
"Can the specific concerns of Indigenous women be addressed within current mainstream feminist and post-colonial discussions? Indigenous Women and Feminism: Politics, Activism, Culture proposes that a dynamic new line of inquiry -- Indigenous feminism -- is necessary to truly engage with the crucial issues of cultural identity, nationalism, and decolonization particular to Indigenous contexts. Through the lenses of politics, activism, and culture, this wide-ranging collection examines the historical roles of Indigenous women, their intellectual and activist work, and the relevance of contemporary literature, art, and performance for an emerging Indigenous feminist project. The questions at the heart of these essays -- What is at stake in conceptualizing Indigenous feminism? How does feminism relate to Indigenous claims to land and sovereignty? What lessons can we learn from the past? How do Indigenous women engage ongoing violence and social and political marginalization? -- cross disciplinary, national, academic, and activist boundaries to explore in depth the unique political and social positions of Indigenous women."--Page 4 de la couverture."A vital and sophisticated discussion that will change the way we think about modern feminism, Indigenous Women and Feminism will be invaluable to scholars, activists, artists, community organizers, and those concerned with Indigenous and feminist issues at home and abroad."-- Résumé de l'éditeur.
Keywords: activisme; approches et analyses; arts; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; militance; pol4105; premier cycle; premières nations; système colonial; systèmes d'oppressions; territoire; thématiques; études autochtones; études féministes; études littéraires

Les subalternes peuvent-elles parler? - Spivak, Gayatri Chakravorty..; Vidal, Jérôme.. (Éd. Amsterdam, 2009)
Dans le cadre d'un dialogue critique avec Michel Foucault, Gilles Deleuze et la tradition marxiste, G.C. Spivak articule le concept de subalterne (à ne pas confondre avec les notions de minoritaire ou d'opprimé) et s'interroge sur les femmes subalternes du tiers-monde, l'unification des subalternes au sein d'une communauté.
Keywords: approches et analyses; arts; care; com5170; corps; cours; discipline; féminisme décolonial; har4600; histoire et politique; incontournable; oui; premier cycle; thématiques; études littéraires; études postcoloniales

Post-colonial studies: The key concepts - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 2000)
This volume provides an essential key to understanding the issues which characterise post-colonialism, explaining what it is, where it is encountered and why it is crucial in forging new cultural identities. As a subject, post-colonial studies stands at the intersection of debates about race, colonialism, gender, politics and language. In the language of post-colonial studies, some words are new, others are familiar words charged with new significance.
Keywords: approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; intersectionnalité; littérature; premier cycle; ressource en ligne; thématiques; études culturelles; études littéraires

Colonialism/postcolonialism - Loomba, Ania (Routledge, 1998)
Colonialism/Postcolonialism est un guide complet mais accessible sur les dimensions historiques, théoriques et politiques des études coloniales et postcoloniales. Ania Loomba examines the key features of the ideologies and history of colonialism, and the relationship of colonial discourse to literature. She goes on to consider the challenges to colonialism, surveying anti-colonial discourses, and recent developments in postcolonial theories and histories. Looking at how sexuality is figured in the texts of colonialism, Colonialism/Postcolonialism shows how contemporary feminist ideas and concepts intersect with those of postcolonialist thought
Keywords: approches et analyses; arts; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; ressource en ligne; thématiques; études littéraires

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Cultural politics, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

The post-colonial studies reader - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 1995)
The Post-Colonial Studies Reader is the most comprehensive selection of key texts in post-colonial theory and criticism yet compiled. This collection covers a huge range of topics, featuring nearly ninety of the discipline's most widely read works. The Reader's 90 extracts are designed to introduce the major issues and debates in the field of post-colonial literary studies. This field itself, however, has become so varied that no collection of readings could encompass every voice which is now giving itself the name "post-colonial." The editors, in order to avoid a volume which is simply a critical canon, have selected works representing arguments with which they do not necessarily agree, but rather which above all stimulate discussion, thought and further exploration. Post-colonial "theory" has occurred in all societies into which the imperial force of Europe has intruded, though not always in the official form of theoretical text. Like the description of any other field the term has come to mean many things, but this volume hinges on one incontestable phenomenon: the "historical fact"of colonialism, and the palpable consequences to which this phenomenon gave rise. The topic involves talk about experience of various kinds: migration, slavery, suppression, resistance, representation, difference, race, gender, place, and reaction to the European influence, and about the fundamental experiences of speaking and writing by which all these come into being. In compiling this reader, the editors have sought to stimulate people to ask: "How might a genuinely post-colonial literary enterprise proceed?" The fourteen sections include: Issues and Debates; Universality and Difference; Textual Representation and Resistance; Postmodernism and Post-Colonialism; Nationalism; Hybridity; Ethnicity and Indigenity; Feminism and Post-Colonialism; Language; The Body and Performance; History; Place; Education; and Production and Consumption. Contributors include many of the leading post-colonial theorists and critics--such as Franz Fanon, Chinua Achebe, Gayatri Chakravorty Spivak, Ngugi wa Thiong'o, Homi Bhabba, Derek Walcott, Edward Said, and Trinh T. Minh-ha--in addition to a number of the discourse's newer voices. The Post-Colonial Studies Reader will prove an authoritative compilation, representing an invaluable contribution to the study of post-colonial theory and criticism.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; périodes historiques; thématiques; études culturelles; études littéraires